Uropod elongation is a common final step in leukocyte extravasation through inflamed vessels - Hyun, Young-Min (The Rockefeller University Press, 2012)
The efficient trafficking of immune cells into peripheral nonlymphoid tissues is key to enact their protective functions. Despite considerable advances in our understanding of cell migration in secondary lymphoid organs, real-time leukocyte recruitment into inflamed tissues is not well characterized. The conventional multistep paradigm of leukocyte extravasation depends on CD18 integrin–mediated events such as rapid arrest and crawling on the surface of the endothelium and transmigration through the endothelial layer. Using enhanced three-dimensional detection of fluorescent CD18 fusion proteins in a newly developed knockin mouse, we report that extravasating leukocytes (neutrophils, monocytes, and T cells) show delayed uropod detachment and become extremely elongated before complete transmigration across the endothelium. Additionally, these cells deposit CD18(+) microparticles at the subendothelial layer before retracting the stretched uropod. Experiments with knockout mice and blocking antibodies reveal that the uropod elongation and microparticle formation are the result of LFA-1–mediated adhesion and VLA-3–mediated cell migration through the vascular basement membrane. These findings suggest that uropod elongation is a final step in the leukocyte extravasation cascade, which may be important for precise regulation of leukocyte recruitment into inflamed tissues.